SURVIVAL PROBABILITY COMPARISON OF DKI JAKARTA RESIDENTS BASED ON GENDER AND MARITAL STATUS - Tri Wahyudi; Samsul Anwar; Ridha Ferdhiana (Universitas Airlangga, 2021)
Human life quality in an area can be determined through the Human Development Index (HDI). One of the fundamental components for the HDI composition is the Life Expectancy Rate (LER). Even though DKI Jakarta Province has a high HDI, research on the factors that influence LER is still fascinating to do. This study aims to compare the survival probability of the DKI Jakarta residents based on gender (male and female) and marital status (unmarried and married) variables. This study analyzed the lifespan data of 464 people who were calculated from birth to death in 2017. The data were analyzed using a lifetime analysis method with a parametric approach which refers to selecting the probability distributions that best fits the research data. The results showed there was no difference in survival probability between the male and female populations. Meanwhile, married residents have a greater survival probability than those who were unmarried. Thus, the Provincial Government of DKI Jakarta needs to increase the percentage of the married population to increase LER, leading to an increase in regional HDI, for example, through economic empowerment programs and optimization of the Planning Generation (GenRe) program.